1998
DOI: 10.1136/jech.52.12.794
|View full text |Cite
|
Sign up to set email alerts
|

Health related lifestyle in adolescence predicts adult educational level: a longitudinal study from Finland

Abstract: Measurements and main results-The outcome variable was the attained educational level at age 24 to 30. Predictive variables described health related lifestyle and health at the age of 16 and 18. Those whose educational level was low at follow up, had in adolescence, a more health compromising lifestyle than those who had reached higher levels. They had placed less emphasis on health promoting behaviours like not smoking, physical exercise, good diet, and dental hygiene. Smoking was the outstanding predictor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
2
45
1
1
Order By: Relevance
“…While some authors have not found any such relationship [16] this link has also been described in other papers [15,38,48]. What is not known is whether good grades and the perception of a good school climate is a cause or a consequence of higher involvement in sport: indeed, Koivusilta et al [27] have shown in a cohort study that adolescents engaging in healthy habits tended to attain a higher level of professional degree later in life.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While some authors have not found any such relationship [16] this link has also been described in other papers [15,38,48]. What is not known is whether good grades and the perception of a good school climate is a cause or a consequence of higher involvement in sport: indeed, Koivusilta et al [27] have shown in a cohort study that adolescents engaging in healthy habits tended to attain a higher level of professional degree later in life.…”
Section: Discussionmentioning
confidence: 71%
“…While some research has tackled the question of correlates of physical activity in general among children and adolescents [26,27,47,55], several studies have specifically focused on the correlates of sport activity [14,16,20,22,49,53]. They usually include socio-demographic, attitudinal and also behavioural factors.…”
Section: Introductionmentioning
confidence: 98%
“…Assessments of SES in adolescents must take into account the transitional nature of the age period and should be conceptualized in two dimensions: familial SES, reflecting the social class of origin, and the adolescent's individual social position in relation to his/her peers [19,20]. The individual social position, when measured by school career or school performance, predicts education in adulthood [19].…”
mentioning
confidence: 99%
“…The individual social position, when measured by school career or school performance, predicts education in adulthood [19]. To assess the SES of adolescents, we used both familial SES (based on family structure, father's/guardian's occupation, father's/guardian's and mother's educational level) and the adolescent's individual social position, based on school performance and school career.…”
mentioning
confidence: 99%
“…Even among individuals who were from a poor background, but had completed high school, the chance of being upwardly mobile socially was higher than those who only had primary level education. 12 In Brazil, according to the IPEA a (2011), the schooling of the population sector with 11 or more years of study increased their relative share in the higher income band (from 40.0% in 1998 to 55.0% in 2008). This trend concerning maternal schooling was observed in this study, with a 29.0% decrease in mothers with ≤ 8 years of study.…”
Section: Discussionmentioning
confidence: 99%